Analisis Hambatan Belajar Peserta Didik terhadap Pelajaran Biologi di Sekolah SMAN 1 Bahorok - Halimatussa’diyah, Enni; Hartono, Adi; Artika, Dewi Nurul; Armiati, Rika (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Education is a conscious effort made to educate and teach students, so that students can develop from those who don't know to know. Learning is said to be successful if the objectives of the learning process carried out can be achieved. Therefore we need a process that provides opportunities for students to actively interact, find knowledge and be able to solve a problem in learning. In this study using quantitative research methods where in this study we conducted 2 classes of SMA Negeri 1 Bahorok. The selection of this sample was carried out by drawing lots of three classes with the same major to take two classes that would be used as research samples (random class in parallel class). This research was conducted in class X at SMA Negeri 1 Bahorok, academic year 2022/2023. The number of samples in this study were 59 students. This sample is divided into 2 classes. This study aims to analyze the learning barriers of students at SMA Negeri 1 Bahorok in class X ipa. The results of this study indicate that students' obstacles in studying Biology generally lie because students lack friends in discussions so that students do not have targets to achieve which causes students to despair. Keywords: Learning Barriers, Biology Lessons